Effect of obesity and exercise training on circulating lipids in American Indian adolescents - Charles F. Hojjat; April M. Teague; Mary A. Tullier; Jennifer Q. Chadwick; Kenneth C. Copeland; Kevin R. Short (PLoS ONE, 2025)
Childhood dyslipidemia is predictive of future cardiometabolic disease. We determined the impact of obesity (Ob) and an exercise program on lipids in American Indian adolescents. This is a secondary analysis from a previously reported trial designed to determine the impact of financial incentives on exercise behavior in American Indian adolescents who were tested in Southeast Oklahoma between June 2013 and January 2017. We performed a cross-sectional comparison of fasting lipids in participants with Ob (n = 74) and a group with normal weight (NW, N = 39) at baseline prior to the exercise intervention. Measurements were repeated for the Ob group after they completed a 16-week exercise program (n = 53). Compared to the NW group, the Ob group at baseline had higher triglycerides (median [interquartile range]: 1.02 [0.67, 1.73] vs. 0.55 [0.40, 0.74] mmol/L), oxidized high density lipoprotein (HDL) (393 [311, 511] vs. 316 [281, 360] ng/mL), oxidized low density lipoprotein (LDL) (49.3 [38.0, 58.6] vs. 38.8 [29.8, 43.4] U/L), and 4 out of 11 targeted fatty acids measured, while HDL-C (mean ± SD: 0.61 ± 0.18 vs. 0.89 ± 0.20 mmol/L) was lower, all p < 0.001. Fatty acid ratios suggested that hepatic lipid metabolism was altered in the Ob group, with higher stearoyl desaturase, and lower elongase and delta-6 desaturase activities. Aerobic fitness increased 10% in the Ob group but among the lipids measured, only elaidic and myristic acid declined in response to exercise. This study is among the first to report that several plasma lipids were altered in American Indian adolescents with Ob and only minor changes occurred following an exercise program. These findings should be interpreted as exploratory and hypothesis-generating, given the study’s observational and secondary analysis design, but highlight the elevated cardiometabolic disease risk in this understudied population and the need for effective prevention and intervention strategies.